The factor that influence employees awareness towards the benefits provided by SOCSO a case study: operation division at Honda Head Office (Malacca Manufacturing Plant) / Mohammad Asyraf Rosrofli and Khairul Azmi Kamal Ariffin - Rosrofli, Mohammad Asyraf; Kamal Ariffin, Khairul Azmi (Faculty of Administrative Science and Policy Studies, 2014)
Nowadays financial security is very important to all people without consider the level of lifestyle they are from. Whether they have high income or low income, everybody want own this protection as much as possible in order to face any risks of losing their income. Thus, people especially who need to bear their family should prepare in term of saving, investment or buy insurance protection with the purpose of handling this possibility. Malaysia government makes a compulsory to all employers to get insurance protection to all their employees named Social Security Organization (SOCSO). However, employees who are government staff, foreign worker, domestic servants, self-employed persons and business owner and spouses of sole-proprietorship or partnership are those exempted from SOCSO coverage. It shows this protection is very important in order to ensure the employee and their family may survive after an incident occurred. Unfortunately, there are still some employees who do not register with SOCSO and several of registered employees less understanding about the role that played by this organization. Therefore, this study will focus on employees awareness towards benefits provided by SOCSO and factor that influence their awareness.